2006
DOI: 10.1111/j.1460-9592.2006.02127.x
|View full text |Cite
|
Sign up to set email alerts
|

ProSealTM as an alternative to endotracheal intubation in pediatric laparoscopy

Abstract: The pediatric PLMA and TT have comparable ventilatory efficacy for elective short laparoscopic procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
65
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 17 publications
10
65
2
1
Order By: Relevance
“…The mean OLP was 29 cm H 2O and Paw after carboperitoneum was 23.79 cm H2O [64]. In a descriptive study, Dave and colleagues successfully used PLMA for ventilating 30 children during LS lasting <60 min.…”
Section: Sad In Paediatric Laparoscopic Surgerymentioning
confidence: 99%
“…The mean OLP was 29 cm H 2O and Paw after carboperitoneum was 23.79 cm H2O [64]. In a descriptive study, Dave and colleagues successfully used PLMA for ventilating 30 children during LS lasting <60 min.…”
Section: Sad In Paediatric Laparoscopic Surgerymentioning
confidence: 99%
“…14 This development has allowed its use to be considered in a wider variety of operative settings where positive pressure would be used routinely. 15 The extent to which the esophageal vent can protect against aspiration is not yet clear.…”
mentioning
confidence: 99%
“…14 Grâce à cette évolution du dispositif, il est maintenant pris en compte dans une plus grande variété de contextes opératoires où la pression positive est généralement utilisée. 15 Il n'est pas clair jusqu'à quel point le conduit oesophagien peut protéger de l'inhalation. Des données limitées existent concernant l'utilisation du COBRA TM chez des enfants, bien qu'il existe des présen-tations de cas rapportant son utilisation réussie pour la bronchoscopie par fibres optiques et chez des enfants pré-sentant des voies aériennes difficiles.…”
unclassified
“…15,16,22,[24][25][26][27][28][29][30][31] Maltby JR et al 2002 did their study with the purpose to compare LMA-PS with ETT with respect to pulmonary ventilation and gastric distention during laparoscopic cholecystectomy. Their result showed that there was no statistically significant difference in SPO2 or ETCO2 between the two groups before or during peritoneal insufflations in either non-obese or obese patients.…”
Section: Discussionmentioning
confidence: 99%